SERUM LIPID PROFILE BASED CLINICAL STUDY OF “MURCCHITA GHRITA” - Archana; Patel Manish Kumar; Netam Narottam; Lalchand; Parhate Saroj (International Journal of Applied Ayurved Research, 2018)
Fat is essential part of our diet. Vitamin A, D, E, K are fat soluble vitamins. Since ancient time in India, ghee is always the preferred source for fat in our diet. Now a days in our society prevalence of Obesity, Cardiovascular and GIT disease is increasing day by day. In the last several decades, ghee has been implicated in the increased prevalence of coronary artery disease (CAD) in Asian Indians due to its content of saturated fatty acids and cholesterol and, in heated ghee , cholesterol oxidation products. There is no any doubt that cow ghee is best source for fat in human diet but there is no any easy method to assure that the ghee which is available in market is pure. So it is clear that we must need such kind of ghee which should have all the beneficial properties without any adverse effect on lipid profile and GIT. Ghrita murchanna is one of the easiest process which can be also perform in kitchen to obtain maximum benefit of ghrit without any drawbacks. In present study we have selected two types of ghrit first one market available ghee made by contemporary method, another one is same ghee but it is used after “Murchhana sanskar”. Comparative study was done to demonstrate the effect of both types of ghee on human lipid profile w.s.r. to LDL/HDL level. Two group of 30 people were selected with a decided dose of 10 gm ghee BD in their diet for four weeks. The results shows that market available ghee increase their LDL/HDL levels and also have GIT problems. Another group which taking Murcchita ghrita (same ghrita after Murcchana) having decrease in LDL/HDL level and having no GIT problem and another hand the group which taking So it is clear that after Murcchana sanskar even ghee made by contemporary method can be used as a substitute of traditional cow ghee as well as ghee that having all beneficial properties.